South Sea Pearls in Lombok, Indonesia: Investigating the Effectiveness of Public Relations in Boosting Aquaculture Tourism - Gandhiwati, Haililah Tri; Rahmanita, Myrza (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
The rich marine resources of Indonesia, epitomized by the South Sea Pearls (SSP) of Lombok, have highlighted the country’s vast potential in the jewellery and tourism sectors. This study delves into the ’aquaculture tourism’ concept by exploring the symbiotic relationship between pearl farming and tourism in Lombok, focusing on the critical role of Public Relations (PR) in amplifying this nexus. Through consultations with multiple stakeholders, this research identifies the power of PR to craft a compelling narrative surrounding the unique qualities of Lombok’s pearls, emphasizing their origins and sustainable farming practices. Key findings suggest that strategic PR can bridge the understanding between tourists, local communities, and industry stakeholders, by fostering two-way communication. The emphasis on sustainable and harmonized practices resonates with global sustainability trends, positioning Lombok as a model for integrating luxury with eco-conscious tourism. This research is a template for regions looking to balance economic growth with environmental responsibility, advocating for a future where luxury and sustainability coexist harmoniously.